Force Convection Heat transfer from a Different Cross Section Cylinder Embedded in Porous Media - Rasheed, Suhad A.; Abood, Jasim M. (Al-Nahrain Journal for Engineering Sciences, 2017)
This research presents an experimental study of forced convection heat transfer for laminar steady flows in a duct filled with saturated porous media glass balls.The heater model consists of a circular cylinder , square cylinder and triangular cylinder .The experimental work was studied the effect of changing heater section on forced convection heat transfer with selected values of heat supply ( 2455W/m2 ).The experiments were carried out for Reynolds number ( 1094 ?